Transient Receptor Potential Channel 6 Knockout Ameliorates Kidney Fibrosis by Inhibition of Epithelial–Mesenchymal Transition - Zhang, Yanhong; Yin, Nina; Sun, Anbang; Wu, Qifang; Hu, Wenzhu; Hou, Xin; Zeng, Xixi; Zhu, Min; Liao, Yanhong (Frontiers in Cell and Developmental Biology, 2021)
Kidney fibrosis is generally confirmed to a significant role in chronic kidney disease resulting in the end-stage kidney failure. Epithelial-mesenchymal transition (EMT) is an important molecular mechanism contributing to fibrosis. Tubular epithelial cells (TEC), the major component of kidney parenchyma, are vulnerable to different types of injuries and as a significant source of myofibroblast by EMT. Furthermore, TRPC6 knockout plays an anti-fibrotic role in ameliorating kidney damage. However, the relationship between TRPC6 and EMT is unknown. In this study, TRPC6-/- and WT mice were subjected to a unilateral ureteric obstruction (UUO) operation. Primary TEC were treated with TGF-β1. Western blot and immunofluorescence data showed that fibrotic injuries alleviated with the inhibition of EMT in TRPC6 -/- mice compared to that of WT mice. The activation of AKT-mTOR and ERK1/2 pathways was down-regulated in the TRPC6-/- mice, while the loss of Na+/K+-ATPase and APQ1 was partially recovered. We conclude that TRPC6 knockout may ameliorate kidney fibrosis by inhibition of EMT through down-regulating the AKT-mTOR and ERK1/2 pathways. This could contribute to the development of effective therapeutic strategies on chronic kidney diseases.